2022
DOI: 10.1021/acsami.2c16483
|View full text |Cite
|
Sign up to set email alerts
|

Pickering Emulsion-Templated Nanocomposite Membranes for Excellent Demulsification and Oil–Water Separation

Abstract: A worldwide steady increase in oily wastewater, due to oil spillage and various industrial discharges, requires immediate efforts toward development of an effective strategy and materials to preserve the natural water bodies. Designing a superwettable fibrous membrane of robust structure and anti-fouling property for efficient separation of oil-water mixtures and emulsions is therefore highly demanding. The electrospun fibrous membrane, which possesses porosity and flexibility and properties including superwet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…It was observed that none of those oils adhered to the membrane surface, implying the versatility of the fabricated membranes in treating various oil emulsions. Such underwater superoleophobicity was ascribed to the formation of a strong hydration layer barrier that prevented the oil droplets from directly interacting with the membrane surface. , The repetitive underwater–oil contact experiment was performed on the EM2 membrane with n -hexane to assess the antifouling nature (Figure A). The membrane exhibited excellent antioil adhesion behavior with no oil stain on its surface.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that none of those oils adhered to the membrane surface, implying the versatility of the fabricated membranes in treating various oil emulsions. Such underwater superoleophobicity was ascribed to the formation of a strong hydration layer barrier that prevented the oil droplets from directly interacting with the membrane surface. , The repetitive underwater–oil contact experiment was performed on the EM2 membrane with n -hexane to assess the antifouling nature (Figure A). The membrane exhibited excellent antioil adhesion behavior with no oil stain on its surface.…”
Section: Resultsmentioning
confidence: 99%
“…PPT@Fe membrane Cetane-in-water 99.5 [33] PVA-TA@SiO 2 coated PTFE membrane Cetane-in-water 99.5 [34] PAAm-TA coated PVDF membrane Toluene-in-water 99.47 [35] Sr-MOF membrane Petrol-in-water 99 [36] Vitrimer epoxy resin membranes Heptane-in-water 98 [37] PNVF@PPM membranes Petrol-in-water 99.5 [38] CoP /SSM n-Hexane-in-water 99.1 [39] ANF/Wood membrane n-Dodecane-in-water 99.37 [2] PVDF-PES membrane Toluene-in-water 99.37 [40] MTNW membrane n-Hexane-in-water 99.60 [41] PI/SDBS membrane n-Hexane-in-water 98.90 [42] CA-DBD membrane Petroleum ether-in-water 99.60 [43] SiO 2 nanocomposite membrane n-Hexane-in-water 99.33 [44] BC composite paper Soybean oil-in-water 99.20 [45] MWCNTs-OH/L-D-Wood Silicone oil-in-water 99.86 This work…”
Section: Materials Emulsion Type Separation Efficiency [%] Referencesmentioning
confidence: 99%
“…Wang et al [26], devised a novel strategy to enhance interfacial adhesion by altering both polypropylene (PP) and cellulose fibre. Maleic anhydride was applied through mechanochemical means to bond it onto PP, thereby enabling interaction with the reactive hydroxyl groups present on the surface of TEMPO-oxidized bamboo cellulose fibre (TBCF).…”
Section: Introductionmentioning
confidence: 99%